Negotiating Classroom Procedures and Routines to Facilitate Students’ Discipline (2022)
ABSTRACT: This study is an action research project carried out with high schoolers at Institucion Educativa Jesus Rey; a public institution located in Robledo, Medellín. The aim of this project was to facilitate the students’ discipline by the implementation of some negotiated classroom procedures and routines. Actions consisted of the creation of a negotiated code of conduct and the implementation of collaborative and cooperative learning in the classroom. Data collection instruments included a teacher journal, two student surveys, and two focus group interviews with the learners. Findings showed that creating a negotiated code of conduct with the students and implementing the different rules and routines could facilitate the students’ discipline and ameliorate the classroom environment.